WASILAH IBADAH AGUNG YANG BANYAK TERSELEWENGKAN - Sawaluddin Siregar (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
Many people mistaken in understanding the nature of Wasilah. Wasilah is one method of praying and one of the doors of the doors to face Allah SWT. If one understands the nature of the wasilah, then he will not easily accuse shirk or disbelief in others, because people who do wasilah also have a strong and strong foundation, both from Al-Qur'an and Hadith, far from shirk, bid'ah And the superstition they have been accusing. God has prescribed for us all kinds of correct, beneficial and objective ways. Such as wasilah with good deeds. The person who performs the prayer, recites the Qur'an or gives alms, means he or she has performed with fasting, prayer, recitation, and alms.